K-NEAREST NEIGHBOR METHOD FOR MONITORING OF PRODUCTION AND PRESERVATION INFORMATION (TREATMENT) OF RUBBER TREE PLANT - Fitria -; Hariyanto Wibowo; Feven Indriyani (Proceeding International Conference on Information Technology and Business, 2018)
The District in Karang Agung Village, the report of production results by the foreman is still done by making regular reports in the foreman's order, supervision of production by the assistant head of the region is still done by looking at reports from the foreman who is still in the form of regular records in the foreman's book and there are still many rubber plants that are not well developed due to lack of knowledge about how to preserve the rubber plants. The methods used have weaknesses, including foremen having difficulty reporting production data because of the distance of plantations and remote plantation offices. In addition, the assistant head of the region was able to find it difficult to monitor production results because the data provided was still in the form of records and is often late by the foreman. The algorithm analysis used the classification method, K-Nearest Neighbor algorithm. A classification method for a set of data based on previously classified data learning. The nearest Neighbor was an approach to finding a case by calculating the proximity between a new case and an old case. It was based on matching the weights of a number of features. Keywords: District, production, K-Nearest Neighbor, Classification